Translation, validity and reliability of decision style scale in forensic psychiatric setting in Indonesia - Natalia Widiasih Raharjanti; Tjhin Wiguna; Agus Purwadianto; Diantha Soemantri; Wresti Indriatmi; Elizabeth Kristi Poerwandari; Marlina S. Mahajudin; Nadia Rahmadiani Nugrahadi; Aisha Emilirosy Roekman; Olivia Jeany Darmawan Adji Saroso; Adhitya Sigit Ramadianto; Monika Kristi Levania (Heliyon, 2022)
Objective: Clinical reasoning as an essential skill for psychiatrists, especially in forensic psychiatry, relies on their thinking and decision-making skills. However, not all psychiatrists are aware of their decision-making styles. This study examines the validity and reliability of the Indonesian translation of the Decision Style Scale (DSS) instrument among general psychiatrists in the Indonesian forensic psychiatry setting. Method: This is a cross-sectional study involving 32 general psychiatrists from all nine psychiatric residency training centers in Indonesia. The study was conducted between August 2020 and February 2021. The translation process involved certified independent translators. The validity was tested using Item-Level Content Validity Index (I-CVI), Scale-Level Level Content Validity Index (S-CVI), and item-total correlation. Internal consistency reliability was measured using Cronbach's alpha. Results: After translation, the instrument was sent back and received feedback from the original authors of DSS. The final version of DSS was valid with an I-CVI score of 0.84–1 and an S-CVI score of 0.99. All but one item had a corrected item-total correlation of more than 0.30. The reliability test of DSS also showed acceptable results with Cronbach's alpha values of 0.43–0.83, and an overall internal consistency score of 0.83 and 0.62 for intuitive and rational scales, respectively. Conclusion: DSS serves as a valid, reliable, and readily-available tool to measure psychiatrists' decision-making styles in forensic psychiatry settings. Enhancing psychiatrists’ awareness of their decision-making styles may help in mitigating the risk of bias in forensic psychiatry evaluations.